2021
DOI: 10.1111/bph.15361
|View full text |Cite
|
Sign up to set email alerts
|

Combining mesenchymal stem cells with serelaxin provides enhanced renoprotection against 1K/DOCA/salt‐induced hypertension

Abstract: Background and Purpose Fibrosis is a hallmark of chronic kidney disease (CKD) that significantly contributes to renal dysfunction, and impairs the efficacy of stem cell‐based therapies. This study determined whether combining bone marrow‐derived mesenchymal stem cells (BM‐MSCs) with the renoprotective effects of recombinant human relaxin (serelaxin) could therapeutically reduce renal fibrosis in mice with one kidney/deoxycorticosterone acetate/salt (1K/DOCA/salt)‐induced hypertension, compared with the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
(130 reference statements)
0
12
0
Order By: Relevance
“…This has been shown to suppress not only Smad 2/3 and consequently, TGF β 1 signalling pathways in cardiac fibroblasts, but also angiotensin II type 2 receptors and interleukin-1 β and the potential interaction of these signalling pathways with the TGF β axis ( Yuan et al, 2017 ; Wu et al, 2018 ), as well as with the inflammasome ( Pinar et al, 2020 ). In addition to those, RLX-2 can increase the expression and activity of matrix metalloproteinases that facilitate ECM degradation ( Li et al, 2021 ). Its application in other diseases, mainly fibrotic, has been postulated, although the clinical trials have been inconclusive on its therapeutic efficacy ( Samuel et al, 2017 ; Yuan et al, 2017 ; Blessing et al, 2019 ; Hinz and Lagares, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to suppress not only Smad 2/3 and consequently, TGF β 1 signalling pathways in cardiac fibroblasts, but also angiotensin II type 2 receptors and interleukin-1 β and the potential interaction of these signalling pathways with the TGF β axis ( Yuan et al, 2017 ; Wu et al, 2018 ), as well as with the inflammasome ( Pinar et al, 2020 ). In addition to those, RLX-2 can increase the expression and activity of matrix metalloproteinases that facilitate ECM degradation ( Li et al, 2021 ). Its application in other diseases, mainly fibrotic, has been postulated, although the clinical trials have been inconclusive on its therapeutic efficacy ( Samuel et al, 2017 ; Yuan et al, 2017 ; Blessing et al, 2019 ; Hinz and Lagares, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of immune cells and NLRP3 inflammasomes have both been implicated in many chronic inflammatory conditions, including hypertension and the associated kidney injury [ 77 ]. BM-MSCs were found to suppress the high-salt-induced assembly and activation of NLRP3 inflammasomes (including NLRP3 and caspase 1) and the downstream production of IL-1β in Dahl salt-sensitive rats and 1K/DOCA/salt-injured mice and inhibit innate (macrophages) and adaptive immune (T cells) components in a murine model of fibrotic nephropathy induced by unilateral ureteral obstruction (UUO) [ 71 ] and 1K/DOCA/salt-induced hypertensive mice [ 72 , 78 ]. Therefore, the ability of BM-MSCs to inhibit inflammasome activity and immune cell infiltration may also explain the anti-hypertensive and anti-inflammatory effects of these stem-cell-based therapies.…”
Section: Mesenchymal-stem-cell-based Therapymentioning
confidence: 99%
“…More recently, evidence has emerged of a novel approach to improve the fibrotic microenvironment of chronically injured kidneys into which BM-MSCs can be administered to improve their survival, migration to site(s) of damage, and reparative efficacy. Recent studies have demonstrated that combining BM-MSCs with the anti-fibrotic and renoprotective agent serelaxin [ 20 , 71 , 72 , 78 ] might provide a more promising alternative (to the strategies described above) to enhance the therapeutic efficacy of BM-MSCs as a treatment for CKD, which is discussed further in the next section.…”
Section: Strategies Used To Enhance Bm-msc-based Therapiesmentioning
confidence: 99%
See 2 more Smart Citations